Grain Productivity, Fertilizer Response and Nutrient Balance of Farming Systems in Tigray, Ethiopia: A Multi‐Perspective View in Relation to Soil Fertility Degradation. (21st October 2014) - Kraaijvanger, Richard; Veldkamp, Tom
Abstract: Application of nutrients is an important way to increase crop productivity. In our study area, Tigray, development agents recommend fertilizer application to boost productivity and counteract nutrient depletion. We analysed soil fertility from different perspectives, using responses and nutrient balances on the basis of on‐farm experimentation. Three perspectives, embedded in the People–Planet–Profit framework and with different temporal and spatial scales and ownership, were considered. Taking a farmer perspective, we found no significant differences in response between recommended and current farmer practices. Taking an agronomist perspective, phosphorus seemed to limit productivity. It however also became obvious that closing nutrient balances at field scale to achieve sustainability is difficult. Only by using considerable amounts of manure and at the cost of productivity this can be achieved. From a long‐term environmentalist perspective, the traditional agricultural system seems sustainable in combining mixed farming and relatively low yields. We conclude that depending on the perspective taken, different interventions will be appropriate. All perspectives however indicate that gradually strengthening the existing mixed farming system by using fertilizers, organic manure and legume fallows supports crop productivity while maintaining other aspects of sustainability such as food security and profitability. In line with this, our analysis of different perspectives suggests that in our study area, farmers will only consider transitions with low risk and this specifically should be addressed in proposing pathways of transition. In processes where stakeholders with different perspectives cooperate, it is important to be aware and make use of the possibilities of comparable multi‐perspective analyses. Copyright © 2014 John Wiley & Sons, Ltd.